1999
DOI: 10.1097/00001756-199901180-00009
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract (EGb 761) protects Na,K-ATPase activity during cerebral ischemia in mice

Abstract: Neuroprotective drugs such as Ginkgo biloba extract (EGb 761) could prevent the ischemia-induced impairment of the Na,K-ATPase activity. In this study, Na,K-ATPase activity and expression, contents in fatty acids and malondialdehyde, an index of lipoperoxidation, were compared in the ipsilateral (ischemic) and the contralateral (unlesioned) cortices after 1 h of unilateral focal cortices cerebral ischemia in the mouse. EGb 761 (110 mg/kg) was administered daily to half of the animals for 10 days before ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 7 publications
1
38
1
Order By: Relevance
“…Experimental work during the last twenty years has also shown that Ginkgo extracts and their constituents, such as ginkgolides and bilobalide, exert beneficial effects in animal models of acute neurodegeneration, e.g. in cerebral hypoxia and ischemia [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work during the last twenty years has also shown that Ginkgo extracts and their constituents, such as ginkgolides and bilobalide, exert beneficial effects in animal models of acute neurodegeneration, e.g. in cerebral hypoxia and ischemia [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Our examination of previous studies showed that the absence of a significant correlation between Group II and Group III or between Group III and Group IV was an expected outcome. This is because earlier studies have reported that GB has a neuroprotective effect against permanent and temporary focal cerebral ischemia (32), that it protects hippocampal neurons against cell death (38), and that it has beneficial effects on various neurodegenerative disorders and peripheral arterial obstruction diseases (34,39). This may be interpreted as GB protecting the brain against injuries that may develop in the brain as a result of ischemia or being effective in overcoming existing injury.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have suggested that GB causes vascular dilatation by inhibiting nitric oxide and thus protecting against hypoxic injury by permitting an increase in blood flow (29,30), and that it improves brain metabolism (31). One study maintained that GB affected cerebral energy metabolism in rats exposed to low-pressure hypoxia and could prolong survival times (32). Some studies have identified an increase in brain glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…The Gingko biloba extract, EGb 761, exerts a neuroprotective effect against permanent and transient focal cerebral ischemia (Pierre et al, 1999;Lee et al, 2002;Chung et al, 2006). EGb 761 also protects hippocampal neurons against cell death induced by beta-amyloid toxicity (Bastianetto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…EGb 761 prevents the neuronal cell death against oxidative stress (Ni et al, 1996). EGb 761 displays neuroprotective actions in animal models of hypoxia and ischemia (Oberpichler et al, 1988;Droy-Lefaix et al, 1995b;Ni et al, 1996;Pierre et al, 1999;Chung et al, 2006). EGb 761 increases the cerebral blood flow and reduces ischemic brain damage (Zhang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%